Comparing Effectiveness of Hand Pollination, Wild Insects and Local Stingless Bees (Tetragonula laeviceps) for Pollination of Exotic Mauritius Raspberry (Rubus rosifolius) - Putra, Ramadhani; Dewangga, Rezha Tanu; Hermawan, Endang; Kinasih, Ida; Raffiudin, Rika; Soesilohadi, RC Hidayat; Purnobasuki, Hery (Bogor Agricultural University, Indonesia, 2024)
Mauritius raspberry (Rubus rosifolius) is an exotic plant cultivated in Indonesia. Studies showed that the productivity of exotic plants is reducing due to a lack of pollination agent for their origin region. Several methods could be applied to overcome this problem. The study aimed to find the most effective method for pollinating this plant among four pollination regimes: Self-pollination, wild insects, stingless bees (Tetragonula laeviceps), and hand-pollination. The observation was conducted on the insect pollinators' activities (visitation rate, flower constancy, and flower handling time), pollination efficiency, and quality of the fruits produced (fruit volume). The results showed a higher visitation rate (10 to 70 per hour), higher flower constancy (visited from 07.00 to 16.00), and longer flower handling time (13.6 s) of T. laeviceps on raspberry flowers than other insects. High activities related to better raspberry pollination success (96%) and bigger fruits produced. Based on this study, applying stingless bees as pollination agents for exotic plants was the best and potentially applicable to other exotic crops.